2019
DOI: 10.1007/s10886-019-01085-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Natural Product Chemistry for Integrated Pest Management of Drosophila suzukii

Abstract: Since the first reports of damage by Drosophila suzukii , the spotted-wing Drosophila (SWD), over a decade ago in Europe, widespread efforts have been made to understand both the ecology and the evolution of this insect pest, especially due to its phylogenetic proximity to one of the original model organisms, D. melanogaster . In addition, researchers have sought to find economically viable solutions for the monitoring and management of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
1
20
1
Order By: Relevance
“…Our results that specific volatile essential oils can be aversive to SWDs are consistent with other laboratory and field studies [32,41]. Previous laboratory studies have also noted that certain essential oils have stronger effects than others [35,41], however, we did not observe any differences under laboratory conditions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results that specific volatile essential oils can be aversive to SWDs are consistent with other laboratory and field studies [32,41]. Previous laboratory studies have also noted that certain essential oils have stronger effects than others [35,41], however, we did not observe any differences under laboratory conditions.…”
Section: Discussionsupporting
confidence: 92%
“…When presented with a choice of oviposition and feeding substrates, SWDs had a greater preference for the untreated diet vials compared to the lavender oil, Ecotrol, or Sporan treated vials (Figure 2). Keesey et al [35] also observed decreased oviposition on substrates treated with Actinidia spp. essential oils, but not for catnip treated substrates.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The last ten years have also brought attention towards another novelty from this group, an agricultural pest species in the form of Drosophila suzukii, which has now invaded North and South America, Europe as well as Asia [5][6][7][8][9] . Furthermore, this pest insect has prompted both integrated pest management efforts as well as evolutionary neuroethology research, where the distinct ecological niche of attacking fresh or ripening fruit has afforded a unique opportunity for comparison among the other model species within this well-studied genus of flies, which usually target softened, fermented host resources [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%